A U-shaped relationship between alcohol consumption and cardiometabolic index in middle-aged men. Issue 1 (December 2016) - Wakabayashi, Ichiro
Abstract Background Cardiometabolic index (CMI) is a new index for discriminating diabetes. The purpose of this study was to determine whether CMI is affected by habitual alcohol drinking. Methods The subjects were 21572 men (35-60 years) receiving annual health checkups. They were divided by average daily ethanol consumption into non-, light (<22 g), moderate (≥22 and < 44 g), heavy (≥44 and < 66 g) and very heavy (≥66 g) drinkers. Relationship between alcohol intake and CMI was investigated with adjustment for age and histories of smoking and regular exercise. Results Log-transformed CMI was significantly lower in light, moderate and heavy drinkers than in nondrinkers and was lowest in light drinkers, while there was no significant difference in log-transformed CMI of nondrinkers and very heavy drinkers. Odds ratio vs. nondrinkers for high CMI was significantly lower than the reference level of 1.00 in light, moderate and heavy drinkers and was lowest in light drinkers but was not significantly different from the reference level in very heavy drinkers. Odds ratio of subjects with vs. those without high CMI for hyperglycemia was significantly higher than the reference level in all of the alcohol groups and was significantly lower in moderate drinkers but was not significantly different in the other drinker groups when compared with the nondrinker group. Conclusion There is a U-shaped relationship between alcohol consumption and CMI, and moderate drinking but not excessive drinking attenuates the association between CMI and hyperglycemia.